(untitled) (Journal of Fatima Jinnah Medical University, 2025)
Background: The improper use and handling of abamectin in agriculture have had major negative effects on human health. As the liver is a key metabolic organ, regular consumption of pesticide residues from fruits and vegetables may increase the risk of hepatotoxicity. This study aimed to evaluate the potential protective effects of pomegranate (Punica granatum) fruit juice extract against abamectin-induced hepatotoxicity in adult albino rats. Subjects and methods: This experimental study was conducted at PGMI and LGH, Lahore, included 24 adult albino rats(6 in each group).Twenty-four Wistar albino rats (180–220 g, 6–8 weeks old) were randomly divided into four groups (n=6 each). Group A served as the control, while Groups B, C, and D were experimental. All groups had free access to water and standard rat food. For 30 days, Group B received abamectin (10 mg/kg), Group C received pomegranate extract (1 mg/kg), and Group D received both treatments (10 mg/kg abamectin + 1 mg/kg pomegranate extract) via oral gavage. On day 30, blood samples were collected for liver enzyme analysis (ALT, AST, and ALP). Rats were sacrificed under general anesthesia, and liver samples were preserved in 10% formalin for histological analysis using Masson’s trichrome and hematoxylin and eosin staining. Liver histology was assessed for toxicity and protection by measuring Hepatocyte size and central vein diameters, observing liver color changes, and analyzing biochemical markers (ALT, AST, and GPX) to evaluate hepatic damage and antioxidant defense. Results: Group B showed significantly increased serum ALT and AST levels, which normalized in Groups C and D. Serum glutathione peroxidase levels were reduced in Group B but restored in Group D. Histological analysis of Group B livers revealed increased central vein diameter, degenerated hepatocytes, nuclear pyknosis, cellular steatosis, sinusoidal congestion, inflammatory cell infiltration, and mild to moderate hepatic fibrosis. Group D showed reduced central vein diameter and partial reversal of histological changes, while Group C exhibited normal liver architecture. Conclusion: Pomegranate juice extract can be used as a very effective dietary supplement to reduce the harmful effects of pesticides such as abamectin